Effect of lightning mast placement on underground power cable jacket stress within high voltage substations - Mostafa Nazih (Journal of Mechatronics, Electrical Power, and Vehicular Technology, 2022)
This study aims to investigate the impact of lightning masts placement on underground cables within high voltage substations. While the subject of lightning discharges near to underground cables has been covered with open cable runs and wind farms in many papers, this study focuses on lightning events within high voltage substations considering the associated effective zones, which were not covered in the available literature. Substations built within areas prone to high lightning activity experience frequent discharges that cause the potential rise of the earthing system into hundreds of kilovolts. The potentials propagating within the soil and the earthing grid affect underground cables jackets terminated within the substation. The numerical analysis of the problem is carried out using Current Distribution, Electromagnetic fields, Grounding and Soil structure analysis (CDEGS) software engine for different configurations of lightning mast placements with varied separation, electrode placement and length, soil resistivity, and lightning current. Study findings indicate that provision of lightning masts/down conductors as far as possible or at least twice the effective zone radius from cable termination/route electrodes ensures relatively lower stress voltages. Electrodes with effective zone radius length placed as close as possible to lightning masts further reduce the attainable jacket stress voltages.